2019
DOI: 10.1177/1369433219866107
|View full text |Cite
|
Sign up to set email alerts
|

Experimental behaviour of concrete-filled steel tubes under cyclic axial compression

Abstract: This study experimentally investigated the behaviour of concrete-filled steel tubes under cyclic axial compression. A total of 42 concrete-filled steel tube specimens of two groups were tested to failure. In each group, 18 specimens were subjected to three cyclic axial loading histories while three specimens were subjected to monotonic loading for comparison. The results indicated that concrete-filled steel tube specimens under cyclic axial compression failed in the form of buckling and still kept their form w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…This confinement was able to eliminate the negative effect of the volumetric instability of slag concrete (Yu et al, 2016). The composite action between steel and concrete of CFST showed improved load carrying capacity and ductility properties compared to conventional reinforced concrete columns (Cao et al, 2020; Ci et al, 2022) and it also helps in minimizing construction costs by reducing the use of formwork (Gupta et al, 2007; Han, 2002; Nematzadeh et al, 2017; Wenchao et al, 2018). Researchers had also studied the effect of stress path dependance on the performance of CFST specimens (Ho et al, 2020; Lai et al, 2020a; Lai et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…This confinement was able to eliminate the negative effect of the volumetric instability of slag concrete (Yu et al, 2016). The composite action between steel and concrete of CFST showed improved load carrying capacity and ductility properties compared to conventional reinforced concrete columns (Cao et al, 2020; Ci et al, 2022) and it also helps in minimizing construction costs by reducing the use of formwork (Gupta et al, 2007; Han, 2002; Nematzadeh et al, 2017; Wenchao et al, 2018). Researchers had also studied the effect of stress path dependance on the performance of CFST specimens (Ho et al, 2020; Lai et al, 2020a; Lai et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Elchalakani et al (2004) tested CFT beam members until fracture under cyclic pure bending with a constant amplitude and compared the peak flexural strength between monotonic and cyclic loading cases. Cao et al (2019) tested 42 CFT columns under axial loading and compared the responses under monotonic loading and cyclic loading with a large number of loading cycles. Their results suggested that the force–displacement relationship was practically identical until the maximum strength.…”
Section: Introductionmentioning
confidence: 99%
“…There are tremendous studies conducted on CFST subjected to different loading types e.g. compression [2][3][4], tension [5,6], cyclic loading [7,8], impact [9,10], etc. Different cross sections of CFSTs have been investigated [11].…”
Section: Introductionmentioning
confidence: 99%
“…Different cross sections of CFSTs have been investigated [11]. Diverse materials have been used to fabricate CFSTs, such as normal/high strength steel [12,13] or stainless steel [14,15]; concrete made of recycled aggregate [3,16,17] or dune sand [18]; and normal [7] or high [2,[19][20][21] strength concrete. To improve the efficiency of CFST, different stiffeners can be employed as reviewed by Alatshan et al [22].…”
Section: Introductionmentioning
confidence: 99%